A benchmarking project on the quality of previous guidelines about the management of malignant pleural effusion from the European Society of Thoracic Surgeons (ESTS) Pleural Diseases Working Group - BATIREL, HASAN FEVZİ (OXFORD UNIV PRESS INC, 2017)
OBJECTIVES: In the European Society of Thoracic Surgeons (ESTS) survey about management of malignant pleural effusions (MPE), 56% of respondents are not informed of any relevant clinical guidelines and 52%, who are aware of the existence of guidelines, declared that they are in need of updating or revision. The ESTS Pleural Diseases Working Group developed a benchmarking project on quality of previous guidelines on the management of MPE. METHODS: The Appraisal of Guidelines for Research and Evaluation (AGREE) II instrument was used to assess each guideline. Each item was scored on a 7-point scale. Scores for each domain were calculated. Economic data for the nations which have issued the guidelines were collected from the Organisation for Economic Cooperation and Development health statistics database. RESULTS: Six guidelines fitted the inclusion criteria and were assessed. Five out of 6 guidelines were produced by a multinational collaboration. Observers would recommend only 2 guidelines with minimal modification. Two areas that received the best score were clarity of presentation and scope and purpose (objectives and health questions target population). The applicability of guideline domain had the lowest score. Multivariate analysis demonstrated that clarity of presentation, international guidelines and publication through medical journal were related to improved scores. A strong correlation was observed between the measures of economic status. CONCLUSIONS: The quality of guidelines assessed by the AGREE II criteria was found to be extremely variable. Guidelines achieving higher AGREE II scores were more likely to come from the European Union with the direct involvement of scientific societies in their development. It was also recognized that some fundamental unanswered questions remain about the management of MPE.
Keywords: Lung cancer; Benchmarking Quality; Malignant pleural effusion; AGREE II; LUNG-CANCER